Astaxanthin suppresses the metastasis of clear cell renal cell carcinoma through ROS scavenging - Jun Gong; Suwei Jiang; Yuanbing Huang; Dongxin Yang; Liang Zhang; Zhenhai Li; Qingzheng Kang (Journal of Functional Foods, 2024)
Clear cell renal cell carcinoma (ccRCC) represents a prevalent form of kidney cancer, and its poor prognosis is closely tied to the occurrence of metastasis. ROS can drive epithelial-mesenchymal transition (EMT), thereby promoting cancer metastasis. Astaxanthin (AXT), renowned for its exceptional antioxidant properties, has been shown in this study to suppress ccRCC metastasis by scavenging ROS. AXT dose-dependently reduced ROS levels and attenuated migratory and invasive capabilities of ccRCC cells. Additionally, ccRCC cells treated with AXT exhibited phenotypic characteristics indicating EMT inhibition, which was reflected by the increased E-cadherin and decreased vimentin. Furthermore, AXT-induced suppressed metastatic potential was also corroborated in mouse lung metastasis model. Notably, artificially elevating ROS levels reversed the AXT-induced reduction in migratory and invasive capacity. Taken together, these findings highlight the anti-metastatic function of AXT in ccRCC, suggesting its therapeutic potential in the management of ccRCC metastasis.